Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's solve the equation step-by-step to determine if it has any solutions:
The equation given is:
[tex]\[ \frac{x}{4x - 16} - 2 = \frac{1}{x - 4} \][/tex]
First, let's simplify and solve the equation.
Step 1: Notice that the denominator [tex]\(4x - 16\)[/tex] can be factored:
[tex]\[ 4x - 16 = 4(x - 4) \][/tex]
So, the equation becomes:
[tex]\[ \frac{x}{4(x - 4)} - 2 = \frac{1}{x - 4} \][/tex]
Step 2: To combine the left side over a common denominator, we need both terms to have the same denominator. The common denominator is [tex]\(4(x - 4)\)[/tex]:
[tex]\[ \frac{x - 2 \cdot 4(x - 4)}{4(x - 4)} = \frac{1}{x - 4} \][/tex]
Simplifying the numerator:
[tex]\[ x - 8(x - 4) = x - 8x + 32 = -7x + 32 \][/tex]
So, the equation now is:
[tex]\[ \frac{-7x + 32}{4(x - 4)} = \frac{1}{x - 4} \][/tex]
Step 3: Since the denominators are equal, we can set the numerators equal to each other:
[tex]\[ -7x + 32 = 4 \][/tex]
Step 4: Solve for [tex]\(x\)[/tex]:
[tex]\[ -7x + 32 = 4 \][/tex]
Subtract 32 from both sides:
[tex]\[ -7x = 4 - 32 \][/tex]
[tex]\[ -7x = -28 \][/tex]
Divide by -7:
[tex]\[ x = 4 \][/tex]
Step 5: Check if [tex]\(x = 4\)[/tex] is a valid solution by substituting in the original equation:
Substitute [tex]\(x = 4\)[/tex] in [tex]\(4x - 16\)[/tex]:
[tex]\[ 4(4) - 16 = 0 \][/tex]
This makes the denominator zero and thus the equation undefined for [tex]\(x = 4\)[/tex].
Therefore, [tex]\(x = 4\)[/tex] is not a valid solution because it leads to division by zero.
Since our earlier steps show [tex]\(x = 4\)[/tex] as the only solution, but it is invalid, we conclude that there are no valid solutions to the equation.
The answer is:
[tex]\[ \boxed{\text{No}} \][/tex]
The equation given is:
[tex]\[ \frac{x}{4x - 16} - 2 = \frac{1}{x - 4} \][/tex]
First, let's simplify and solve the equation.
Step 1: Notice that the denominator [tex]\(4x - 16\)[/tex] can be factored:
[tex]\[ 4x - 16 = 4(x - 4) \][/tex]
So, the equation becomes:
[tex]\[ \frac{x}{4(x - 4)} - 2 = \frac{1}{x - 4} \][/tex]
Step 2: To combine the left side over a common denominator, we need both terms to have the same denominator. The common denominator is [tex]\(4(x - 4)\)[/tex]:
[tex]\[ \frac{x - 2 \cdot 4(x - 4)}{4(x - 4)} = \frac{1}{x - 4} \][/tex]
Simplifying the numerator:
[tex]\[ x - 8(x - 4) = x - 8x + 32 = -7x + 32 \][/tex]
So, the equation now is:
[tex]\[ \frac{-7x + 32}{4(x - 4)} = \frac{1}{x - 4} \][/tex]
Step 3: Since the denominators are equal, we can set the numerators equal to each other:
[tex]\[ -7x + 32 = 4 \][/tex]
Step 4: Solve for [tex]\(x\)[/tex]:
[tex]\[ -7x + 32 = 4 \][/tex]
Subtract 32 from both sides:
[tex]\[ -7x = 4 - 32 \][/tex]
[tex]\[ -7x = -28 \][/tex]
Divide by -7:
[tex]\[ x = 4 \][/tex]
Step 5: Check if [tex]\(x = 4\)[/tex] is a valid solution by substituting in the original equation:
Substitute [tex]\(x = 4\)[/tex] in [tex]\(4x - 16\)[/tex]:
[tex]\[ 4(4) - 16 = 0 \][/tex]
This makes the denominator zero and thus the equation undefined for [tex]\(x = 4\)[/tex].
Therefore, [tex]\(x = 4\)[/tex] is not a valid solution because it leads to division by zero.
Since our earlier steps show [tex]\(x = 4\)[/tex] as the only solution, but it is invalid, we conclude that there are no valid solutions to the equation.
The answer is:
[tex]\[ \boxed{\text{No}} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.